Currículo Paulista de História: distanciamentos e aproximações da concepção freireana de currículo a partir das categorias realidade concreta, diálogo e práxis - Costa, Antonio de Pádua Oliveira (2022)
This dissertation is a result of the research that had as main objective to analyze the Paulista Curriculum of History in the Elementary School stage in the light of Paulo Freire's pedagogy, seeking to identify distances and approximations of the Freirean conception of curriculum from the categories concrete reality, dialogue and praxis. The relevance of this research lies in the fact that the Currículo Paulista de História is a prescriptive document for the pedagogical practices developed in the classroom by teachers and students of the Public Education Network of the State of São Paulo. Through a qualitative approach, we resorted to bibliographic research and document analysis, establishing the Discursive Textual Analysis as a method of document analysis, aiming to understand how the consolidation of History as a school discipline took place from the process of constitution of its curricula and programs, what are the characteristics of the Traditional, Critical and Post-Critical curricula, the foundations of Paulo Freire's critical curriculum and what are the distances and approximations of the Paulista Curriculum of History, of the Freirean critical curriculum conception. For this understanding, we turn to the works of Bittencourt (2010), Abud (2004), Júnior (2013), Mathias (2011), Nadai (1993), Toledo (2005), Santos (2009), Fonseca (2003), Goodson (1997), Silva (2005), Sacristán (2013), Moreira and Tadeu (2011), Lopes and Macedo (2011), Moraes (2003), Lüdke and André (2018) and Chizzotti (2006). At the same time, we used the works Pedagogy of the Oppressed (2019), Extension or Communication? (2020) and Cultural Action for Freedom and other writings (2006) to support Freire's analytical categories concrete reality, dialogue and praxis. The main results of the research show that the Paulista Curriculum of History does not approach the conception of a critical Freirean curriculum, as it does not contemplate in a clear and objective way the categories concrete reality, dialogue and praxis, approaching more of a perspective of Traditional Curriculum, by acting as a guiding and prescriptive document of content and practices for students and teachers.